PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII SMPN 1 KAMANG MAGEK - Putri, Meisya Rahma (Departemen Matematika, 2024)
Grasping mathematical concepts is deemed an essential capability that students ought to acquire. However, preliminary evaluations at SMPN 1 Kamang Magek revealed a deficiency in pupils' Mathematical Concept Understanding. An effective resolution to this dilemma is the implementation of the Numbered Head Together cooperative learning strategy. This investigation is characterized by descriptive and quasi-experimental methodologies, employing a non-equivalent pretest-posttest control group framework. The subject pool encompassed eighth graders from SMPN 1 Kamang Magek during the 2024/2025 academic period. Saturated Sampling was implemented for selecting participants. Employed as tools for measurement in this analysis were quizzes along with tests assessing Mathematical Concept Understanding (Pretest and Posttest). Derived from the analysis of quiz data, an enhancement was observed in the Mathematical Concept Understanding of learners in the experimental group throughout the employment of the Numbered Head Together type collaborative educational method. The data from the Mathematical Concept Understanding test indicated that, with an alpha of 0.05, a P-value of less than 0.000 was procured, thereby leading to the rejection of the null hypothesis. It has been deduced that students employing the Numbered Head Together cooperative learning approach exhibit superior Mathematical Concept Understanding compared to those engaging in Direct Learning.Keywords– Mathematical Concept Understanding, Direct Learning, Numbered Head Together